Technique types of preparatory and take-off motions for elite male long jumpers - Shimizu, Y.; Ae, M.; Fujii, N.; Koyama, H. (International Journal of Sport & Health Science, 2018)
The purposes of this study were to classify jumping techniques in the preparatory and take-off phases of elite male long jumpers in official competitions by using a cluster analysis and to identify biomechanical characteristics of classified technique types. The preparatory and take-off motions of 29 elite male long jumpers in official competitions were collected three-dimensionally using two high-speed cameras. Their jumps were classified into four types of jumping technique by using the Ward`s method of cluster analysis with the take-off angle as a parameter. The four types were named the Horizontal (H-type), Semi-Horizontal (SH-type), Semi-Vertical (SV-type), and Vertical (V-type) types. There were no significant differences in jumping distance among the types. H-type jumpers were characterised by a forward lean of the trunk and a larger swing leg knee flexion during the preparatory phase. V-type jumpers flexed the knee joint of the support leg more during support phase in the last stride and showed a larger backward lean of the trunk at touchdown of the take-off foot. SH- and SV-types were located between H-type and V-type jumpers. This classification will help coaches and jumpers to select appropriate techniques.